2022
DOI: 10.1002/solr.202200335
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Methane Conversion to C1 Oxygenates over Palladium and Oxygen Vacancies Co‐Decorated TiO2

Abstract: As the principal constituent of natural/shale gases, methane (CH 4 ) is a promising industrial feedstock for manufacturing value-added chemicals. [1] However, efficient CH 4 conversion is still of a great challenge owing to its high C-H bond energy (439 kJ mol À1 ), low electron affinity (À1.9 eV), and high ionization energy (12.6 eV). [2] The current industrial CH 4 conversion via dry/steam-reforming [3] and subsequent Fischer-Tropsch synthesis [4] is an energy-intensive and indirect route, where high temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…To further confirm the existence of oxygen vacancy, low-temperature EPR (Figure d) was performed. The paramagnetic signal centered at g = 2.003, which can be assigned to the typical response of O V , was identified for various catalysts. , The peak intensity was enhanced after the addition of Cu and reached the highest value for 2Cu/CeO 2 . The introduction of metals has been reported to promote the formation of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 97%
“…To further confirm the existence of oxygen vacancy, low-temperature EPR (Figure d) was performed. The paramagnetic signal centered at g = 2.003, which can be assigned to the typical response of O V , was identified for various catalysts. , The peak intensity was enhanced after the addition of Cu and reached the highest value for 2Cu/CeO 2 . The introduction of metals has been reported to promote the formation of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 97%
“…In the EPR spectrum of 0.5Pd‐ZnTi‐LDH‐A200 shown in Figure 4d, the signal peak at g = 2.076 is assigned to the adsorbed oxygen, indicating the efficient adsorption of O 2 molecules. [ 40,49 ] The signal peak at g = 2.028 is attributed to the oxygen radicals of O −· (Ti 4+ O 2− Ti 4+ O −· ), [ 42,54,55 ] which was reported to be formed by the trapping of photoproduced holes. ERP tests indicate that Pd loading is conductive to the adsorption of O 2 molecules on the defective site of ZnTi‐LDH, which may result in the generation of more reactive oxygen species and enhanced CH 4 oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3c, the original ZnTi-LDH without calcination and Pd loading shows very poor performance for CH 4 conversion with only a slow rate of HCHO production (299.95 μmol g −1 h −1 ). It is widely reported that co-catalyst loading is beneficial to improve the activity of photocatalysts, [40,49] herein Pd was photo deposited on the surface of the prepared ZnTi-LDH. However, the activity improvement for C 1 products is very limited by Pd loading, which is only 1.8 times higher (557.13 μmol g −1 h −1 ) than the unloaded ZnTi-LDH.…”
Section: Photocatalytic Ch 4 Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the fact that the presence of oxygen in the solution limits the risks of hole/electron recombination. Indeed, the oxygen molecules, absorbed on the surface of the photocatalyst, act as very effective traps of electrons from the conduction band, thus totally or partially suppressing the recombination of surface electron-hole pairs [22]. As a result, the formation of hydroxyl radicals (˚OH) and other reactive species, responsible for the degradation of the pollutant, will be improved.…”
Section: Influence Of Oxygen In the Airmentioning
confidence: 99%